Risk Society, Bioethics and the Precautionary Principle - Santos, Marcelo Pereira dos (2015)
The dynamics of medicine has causing great shiver in society, given the progress made in the context of biomedicine and genetic events that provided before thoughtless as the assisted reproduction techniques, therapeutic cloning, surgery for transmutation of sex, as well as focused clinical procedures prolonging life. These events do not occur without causing ethical dilemmas that require a reflection on the limits and degrees of acceptability in the methods and practices used by health professionals, biologists, scientists, pharmacists and others involved in the manipulation of genetic material and trials with humans. From this perspective, this paper, from the analytical assessment of the Bioethics paradigms, promotes the correlation between human dignity, scientific progress and rights of future generations under inflows arising from advances in science and technology in a society of risk and the ambivalence. The analysis of the issues is promoted with the use of dialectical-descriptive methodology, based on the literature about the above issues, involving books, articles, dissertations and theses published in the last ten years. The theoretical framework sits in the design of risks and ambivalences, outlined by Ulrich Beck, Franz Josef Brüseke, Anthony Giddens, Zygmunt Bauman. The study aims to understand the necessary effect bioethics of the precautionary principle as a guiding ethical beacon of scientific and technical progress and the necessary reconciliation between trials and legitimacy of choices for the maintenance and evolution of the human species.